Cross-cultural communication experiences among international sojourners in Malaysian universities / Massila Hamzah - Hamzah, Massila (Institute of Graduate Studies, UiTM, 2015)
This qualitative study focuses on cross-cultural communication experiences among international sojourners (IS) in Malaysian universities. Four research objectives were addressed : 1) to identify the transition shock symptoms in cross-culture communication faced by the international sojourners in Malaysian universities, 2) to determine the building blocks faced by international sojourners in cross-cultural transition, 3) to identify the aspects of perceived similarities or differences by international sojourners in their manifestations of culture 4) to ascertain the adaptation strategies embraced by international sojourners in overcoming cross-cultural communication challenges. Salient discoveries were obtained through in-depth interview with fifteen IS residing in Malaysian universities. The findings painted a vivid picture of the sojourning experiences. Firstly, the symptoms of transition shock were highly characterized by initial sojourning experiences, home separation struggles, emotional distress, initial communication-related stress and acclimatizing to surrounding. Initial sojourning anticipations contributed to themes of: i) unexpected encounters ii) felt differences iii) influences of past experiences. Home separation verify various struggles along the themes of : i) homesickness, ii) attachment need and iii) nostalgic feeling. Indications of emotional distress derived to themes of: i) affective upheavals, ii) yearning to leave and iii) challenged by strangeness. Initial communicationrelated symptom were salient in themes of : i) initial engagement challenges ii) interaction gap, and iii) withdrawal. Acclimatizing to the surroundings contributed to themes of : i) weather condition, and ii) food acceptance. Secondly, findings warranted the building blocks in cross-culture transition were associated to communication tribulations, language barriers and cross-cultural disputes…